Book review:E. TCHKOIDZE, Ένας Γεωργιανός προσκυνητής στον βυζαντινό κόσμο του 9ου αιώνα: ο Άγιος Ιλαρίων ο Γεωργιανός [A Georgian Pilgrim in the Byzantine World of the 9th Century: Saint Hilarion the Georgian], Athens 2011, 273 pp. (ISBN 978-960-6813-29 - PREISER-KAPELLER, Johannes (Byzantina Symmeikta, 2016)
BOOK REVIEW:: E. Tchkoidze, Ένας Γεωργιανός προσκυνητής στον βυζαντινό κόσμο του 9ου αιώνα: ο Άγιος Ιλαρίων ο Γεωργιανός [A Georgian Pilgrim in the Byzantine World of the 9th Century: Saint Hilarion the Georgian], Athens 2011, 273 pp. (ISBN 978-960-6813-29-0)